Risk perceptions of avian influenza among poultry farmers on smallholder farms along border areas of Thailand - Hinjoy, Soawapak; Thumrin, Pornchai; Sridet, Jitphanu; Chaiyaso, Chat; Smithsuwan, Punnarai; Rodchangphuen, Janjao; Thukngamdee, Yupawat; Suddee, Weerachai (Frontiers in Veterinary Science, 2023)
Introduction Thailand has not reported any cases of avian influenza since 2008. However, avian influenza viruses circulating in poultry in neighboring countries may have potential for transmission to humans. The aim of this study was to assess risk perceptions of poultry farmers and traders in three border provinces of Thailand adjacent to Laos. Materials and methods Poultry farmers and traders were interviewed in-person during October – December 2021 by health and livestock officials using a standardized questionnaire to collect demographics, job histories, knowledge, and practices related to avian influenza. Knowledge and practices were scored using 22 questions with a 5-point scale. Exploratory data analysis scores above and below the 25th percentile was used as the cut-off point for perception scores. The cut-off point was used to describe perceptions of respondent characteristics in order to compare differences between groups with more or less than 10 years of experience. Age adjusted perceptions of disease risk were analyzed by multivariable logistic regression. Results Of the 346 respondents, the median risk perception score was 77.3% (22 questions with a 5-point scale, so the total score was 110). Having more than 10 years of experience in poultry farming was significantly associated with an increased perception of the risk of avian influenza (adjusted odds ratio 3.9, 95% confidence interval 1.1–15.1). Thirty-two percent of participants perceived avian influenza as a risk only during the winter season, and more than one-third of the participants (34.4%) had not received recent information about new viral strains of avian influenza. Discussion Participants did not perceive some key information on the risks associated with avian influenza. Regular training on the risks of avian influenza could be provided by national, provincial and/or local officials and they, in turn, could share what they learn with their communities. Participants who had greater experience in poultry farming were associated with greater risk perception. Experienced poultry farmers and traders working on poultry farms can be a part of the community mentorship program to share their experiences and knowledge on avian influenza with new poultry producers to improve their perception of disease risk.